Supplier development in a multi-tier supply chain. (2nd April 2020) - Karaer, Özgen; Kraft, Tim; Yalçın, Pınar
Abstract: We examine how a buyer can use a full-control strategy and cost sharing to develop the sustainable quality capabilities of his tier-1 and tier-2 suppliers. In particular, we consider how the buyer's development decisions and the suppliers' sustainable quality decisions are impacted by consumers' demand sensitivity to sustainable quality and the division of the supply chain margin. Two quality-demand models are studied – the overall quality of the supply chain equals either (i) the sum of or (ii) the minimum between the suppliers' quality levels. We find that when the suppliers' sustainable quality levels are additive, even if the low-margin supplier has a positive net profit return from improved quality, she may still choose to free ride on the high-margin supplier's quality investment. Interestingly, the buyer can cause the free riding with his cost-sharing decisions. When instead, the overall sustainable quality is determined by the minimum between the suppliers' quality levels, the buyer's strategy is often to focus only on developing the low-margin supplier. Nevertheless, when the buyer's market gain from improved quality is large and the suppliers' gains are comparable to one another, the buyer can justify sharing costs with both suppliers and raising the overall sustainable quality of the supply chain to a level neither supplier can achieve without development support.